Towards Sustainable Development of Islamic Higher Education: A Meta-Analysis of Challenges and Opportunities - Desmaniar; Rusli; Aqil Teguh Fathani; Novia Amirah Azmi; Muhammad Mughni; Imam Rasikh Islami; Abdan Syukri (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2022)
This paper aims to describe the challenges and opportunities in the growth of sustainable development of Islamic higher education in Indonesia to construct an effective management system in terms of both quality and quantity. Such a system should enable us to evaluate the effectiveness of Islamic education in combating radicalization, terrorism, and sexual harassment, as well as promoting efforts to expand human resources. The Scopus database was searched for articles on